A 12‐year radar‐based climatology of daily and sub‐daily extreme precipitation over the Swiss Alps. (6th April 2018) - Panziera, L.; Gabella, M.; Germann, U.; Martius, O.
Abstract : The characterization of the alpine extreme precipitation is the basis to study the projected changes in frequency and intensity of heavy rainfall and is needed to improve the resilience of communities to high‐impact weather. Climatological features of extreme daily and sub‐daily precipitation are documented here for the Swiss Alps and surrounding regions at a high spatial resolution (1 km 2 ). The basis is 12 years of data from rain gauges and CombiPrecip, a rainfall field produced by locally adjusting the radar precipitation map to the values measured by rain gauges. The agreement between rain gauges and CombiPrecip concerning both the timing and the magnitude of the extreme events is quantified by cross‐validation; overall, it increases with diminishing the severity of the extremes and increasing accumulation time. If the extremes represent on average the 10 most intense rainfall accumulations per year, in general 50–65% of rain gauges extremes are extremes also for CombiPrecip, 40–50% of CombiPrecip extremes are not extremes according to rain gauges, and CombiPrecip extremes are till 7% lower than rain gauges extremes. The maps presented in this paper show that both daily and sub‐daily extremes are more intense along the alpine slopes compared to the crest of the Alps in all seasons, with the Lago Maggiore region showing the largest values. The fraction of yearly rainfall due to extremes is generally smaller in the Alps than in flat terrain. Extreme 1‐hr precipitation is more clustered in time in the inner Alps, but is less frequent, and exhibits a strong diurnal cycle in summer. The paper also shows that sub‐daily and daily extremes occur essentially over the same 24‐hr period. Abstract : Climatological features of extreme daily and sub‐daily precipitation are documented for the Swiss Alps and surrounding regions at a high spatial resolution based on 12 years of merged radar and rain gauges data. The agreement between rain gauges and the radar‐derived precipitation concerning both the timing and the magnitude of the extreme events is quantified by cross‐validation. The maps presented in this paper show interesting features of both daily and sub‐daily extremes, an excellent basis for climate models validation.